Comparison of skeletal muscle ultrastructural changes between normal and blood flow-restricted resistance exercise: A case report - Wilburn, D. T.; Machek, S. B.; Zechmann, B.; Willoughby, D. S. (Experimental Physiology, 2021)
New findings What is the main observation in this case? The main observation of this case report is that blood flow-restricted exercise can cause myofibrils to have an aberrant wave-like appearance that is accompanied by irregular pockets of sarcoplasm in the intermyofibrillar space, while traditional forms of damage to the Z-discs and contractile elements are not as apparent. What insights does it reveal? Our findings indicate that blood flow restriction-mediated fluid pooling might cause alterations in skeletal muscle ultrastructure after exercise that might be directly related to myofibre swelling. Abstract The acute effects of blood flow-restricted (BFR) exercise training on skeletal muscle ultrastructure are poorly understood owing to inconsistent findings and the use of largely imprecise systemic markers for indications of muscle damage. The purpose of this study was to compare myofibrillar ultrastructure before and 30 min after normal and BFR resistance exercise using transmission electron microscopy in a single individual to evaluate the feasibility of this more nuanced approach. One apparently healthy male with 13 years of resistance exercise completed six sets of both BFR [30% of one-repetition maximum (1-RM)] and normal non-occluded (70% of 1-RM) unilateral angled leg press on the contralateral leg, as a control, after assessment of 1-RM 72 h before. Vastus lateralis muscle biopsies were collected before and 30 min after each exercise session. The lengths and widths of 250 sarcomeres and the sarcoplasmic area were assessed via 20 individual transmission electron photomicrographs. Analysis revealed that BFR training (1.769 ± 0.12 µm) increased sarcomere length when compared with normal exercise (1.64 ± 0.17 µm; P < 0.001), without differences in sarcomere width between conditions (BFR, 0.90 ± 0.26 µm; normal, 0.93 ± 0.27 µm; P = 0.172). Furthermore, there were no significant interaction (P = 0.168) or condition effects between BFR (25.98 ± 4.17%) and normal (27.3 ± 6.49%) resistance exercise for sarcoplasmic area (P = 0.229). Exercise also increased sarcoplasmic area within the myofibril (pre-exercise, 24.42 ± 5.13%; postexercise, 28.95 ± 5.92%) for both conditions (P = 0.001). This case study demonstrates a unique BFR training-induced alteration in myofibril ultrastructure that appeared wave like and was accompanied by intracellular abnormalities that appeared to be fluid pockets of sarcoplasm disrupting the surrounding myofibrils.